Orientation dependent spheroidization response and macro-zone formation during sub β-transus processing of Ti-6Al-4V alloy. (1st August 2017) - Roy, Shibayan; Suwas, Satyam
Abstract: In the present study, sub β-transus static annealing was carried out on a (α+β)-warm-rolled (700 °C, 90% thickness reduction) Ti-6Al-4V alloy at 900 °C for various durations (15, 30, 45, 60, 75 and 90 min). The key observation was that the spheroidization response of the constituent α-colonies from the starting warm-rolled material differs significantly during subsequent (α+β)-annealing treatment. While some of the α-colonies underwent an early morphological conversion from lamellar to equiaxed, some others stayed stable for prolonged durations. This unique phenomenon has been examined, for the first time, from an orientation perspective by coupling slip activation, boundary formation, and interfacial energy anisotropy of individual α-colonies with their response to static spheroidization. Orientation of the α-colonies in reference to the loading directions dictate the nature of slip activation (single versus multiple slip; basal or prism slip plus pyramidal 〈c+a〉 slip) during prior (α+β)-rolling. During subsequent static (α+β)-annealing, this factor translates into the relative ease of boundary splitting and thermal grooving for them. Formation of longitudinal boundaries, then set the order of spheroidization for diffusion based coarsening processes during long term annealing. Anisotropy in interfacial energy, owing to the loss of coherency during prior deformation (warm-rolling), creates further orientation dependency in the spheroidization sequence. An immediate consequence of this orientation dependent spheroidization response is realized in the formation of the macro-zones for two-phase Titanium alloys after secondary thermomechanical processing. Some remedial processing strategies are highlighted therein. Graphical abstract: